Telovelar Approach for the Surgical Resection of a Caudal Fossa Glioma in a Toy Poodle - Victoria Kymm; Youngjin Jeon; Il-Hwa Hong; Yoonho Roh (Animals)
A 7-year-old, 6.5 kg, neutered male toy poodle presented with tetraparesis, characterized by lower motor neuron signs in the forelimbs and upper motor neuron signs in the hindlimbs, along with seizures. Diagnostic imaging using magnetic resonance imaging (MRI) and computed tomography (CT) revealed a 1.4 cm × 1.4 cm × 2.2 cm mass in the fourth ventricle and caudal part of the brainstem. The surgical objective was to precisely remove masses compressing the cerebellum and brainstem. Using the telovelar approach, the tumor was partially excised, contrary to the goal of complete removal. Histopathological analysis confirmed the diagnosis of glioma. By the third postoperative day, the patient began to walk independently, and tetra-ataxia symptoms gradually decreased. Postoperative imaging confirmed the successful debulking of the tumor. By postoperative day 15, the patient showed normal gait, and adjuvant radiation therapy (RT) was initiated 2 weeks later. Unfortunately, the patient died 91 days after surgery, though the precise cause of death remains undetermined.